The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/0103-11042018s417
|View full text |Cite
|
Sign up to set email alerts
|

Análise das notificações de intoxicações agudas, por agrotóxicos, em 38 municípios do estado do Paraná

Abstract: RESUMO O Paraná é o segundo maior consumidor de agrotóxicos no Brasil, e sua notificação de intoxicações agudas não corresponde a esta realidade. Objetivou-se verificar a correlação entre consumo de agrotóxicos em municípios do Paraná e notificação de intoxicações agudas. Analisaram-se bancos de dados do consumo de agrotóxicos e da ocorrência de intoxicações. Foram realizadas entrevistas com agentes da vigilância epidemiológica, para compreender o processo de identificação e notificação dos casos. Não se evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 7 publications
2
2
0
18
Order By: Relevance
“…17 In our research, the main symptoms of acute intoxications reported by participants were dizziness, headache and nausea. These findings are in agreement with Taveira and Albuquerque (18) who, when analyzing a pesticides use database, showed symptoms of dizziness and nausea, among others, to be the most reported in the Brazilian state of Paraná. 18 The findings of this study revealed greater occurrence of acute intoxication in males than in females.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…17 In our research, the main symptoms of acute intoxications reported by participants were dizziness, headache and nausea. These findings are in agreement with Taveira and Albuquerque (18) who, when analyzing a pesticides use database, showed symptoms of dizziness and nausea, among others, to be the most reported in the Brazilian state of Paraná. 18 The findings of this study revealed greater occurrence of acute intoxication in males than in females.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in agreement with Taveira and Albuquerque (18) who, when analyzing a pesticides use database, showed symptoms of dizziness and nausea, among others, to be the most reported in the Brazilian state of Paraná. 18 The findings of this study revealed greater occurrence of acute intoxication in males than in females. Silva (19) also found that males working in agriculture had higher intoxication incidence rates and considered them to be a group at greater risk.…”
Section: Discussionsupporting
confidence: 92%
“…Entre os grupos mais afetados pelos danos gerados pelas substâncias químicas agrícolas, encontra-se o dos trabalhadores da agricultura e da pecuária, que são vulneráveis aos agrotóxicos desde o preparo, manipulação até o armazenamento nos recipientes após o uso (Taveira, Albuquerque, 2018).…”
Section: Resultsunclassified
“…Para além da utilização de agrotóxicos na produção de alimentos, encontra-se a intoxicação de trabalhadores pelo uso indevido dos agrotóxicos. Segundo os dados publicados pela Organização Internacional do Trabalho (OIT)/Organização Mundial da Saúde (OMS), aproximadamente 70 mil trabalhadores de distintos países foram a óbito por consequência de intoxicações agudas e crônicas por uso indevido de agrotóxicos (Faria et al, 2007;Taveira & Albuquerque, 2018).…”
Section: Uso Dos Agrotóxicosunclassified
“…O processo de intoxicação por uso de agrotóxicos pode acontecer em distintos mecanismos, sendo eles por via digestiva, respiratória, dérmica e/ou por contato ocular, acarretando conjuntos de sintomas com características agudas, subagudos ou crônicos. Entre os grupos mais afetados pelos danos determinados pelas substâncias químicas agrícolas, encontra-se os trabalhadores da agricultura e da pecuária, que são vulneráveis aos agrotóxicos desde o preparo, manipulação até armazenamento dos recipientes após o uso (Taveira & Albuquerque, 2018).…”
Section: Uso Dos Agrotóxicosunclassified